Digital soil mapping and assessment for Australia and beyond: A propitious future - Searle, Ross; McBratney, Alexander; Grundy, Mike; Kidd, Darren; Malone, Brendan; Arrouays, Dominique; Stockman, Uta; Zund, Peter; Wilson, Peter; Wilford, John; Van Gool, Dennis; Triantafilis, John; et al. (Geoderma Regional, 2021)
Digital Soil Mapping and Assessment (DSMA) has progressed from challenging traditional soil science paradigms, through small scale prototyping, to large-scale implementation capturing quantitative measures of soil attributes and functions. This paper considers the future for DSMA in the context of a highly uncertain world where high-quality knowledge of soil dynamics will be important for responding to the challenges of sustainability. Irrespective of whether the need is for survival, increased productivity or broadening the services provided from land management, or simply securing the soil itself, we see DSMA as a fundamental approach and essential tool. With a broadening need and a strong foundation in the practice of DSMA now in place, the theory, tools and technology of DSMA will grow significantly. We explore expected changes in covariate data, the modelling process, the nature of base data generation and product delivery that will lead to tracking and forecasting a much wider range of soil attributes and functions at finer spatial and temporal resolutions over larger areas, particularly globally. Equally importantly, we expect the application and impact of DSMA to broaden and be used, directly and collaterally, in the analysis of land management issues in coming decades. It has the capacity to provide the background to a soil and landscape ‘digital twin’ and the consequent transformation in monitoring and forecasting the impacts of land management practices. We envision the continued growth of DSMA skills amongst soil scientists and a much broader community of practice involved in developing and utilizing DSMA products and tools. Consequently, there will be a widening and deepening role of public-private partnerships in this development and application. •Digital Soil Mapping and Assessment (DSMA) has progressed from the research domain to large-scale implementation.•We examine the possible future development and application paths for DSMA.•We explore expected changes in DSMA inputs, methods, outputs and uses.•We expect in the future the application and impact of DSMA will broaden and be widely used in land management.